Informing Consumers about their own Preferences - Martin Peitz; Roman Inderst (University of Mannheim, Department of Economics, 2012)
We analyze a model of monopolistic price discrimination where only some consumers are originally sufficiently informed about their preferences, e.g., about their future demand for a utility such as electricity or telecommunication. When more consumers become informed, we show that this benefits also those consumers who remain uninformed, as it reduces the firm's incentives to extract information rent. By reducing the costs of information acquisition or forcing firms to supply consumers with the respective information about past usage, policy can further improve welfare, as contracts become more efficient. The last observation stands in contrast to earlier findings by Crémer and Khalil (American Economic Review 1992), where all consumers are uninformed.
urn:nbn:de:bsz:180-madoc-313251
Keywords: D42; D82; L12; 330; Nonlinear pricing; price discrimination; monopolistic screening; information acquisition